Functional heterogeneity in the left lateral posterior parietal cortex during visual and haptic crossmodal dot‐surface matching. Issue 3 (19th January 2021) - Yang, Jiajia; Yu, Yinghua; Shigemasu, Hiroaki; Kadota, Hiroshi; Nakahara, Kiyoshi; Kochiyama, Takanori; Ejima, Yoshimichi; Wu, Jinglong
Abstract: Background: Vision and touch are thought to contribute information to object perception in an independent but complementary manner. The left lateral posterior parietal cortex (LPPC) has long been associated with multisensory information processing, and it plays an important role in visual and haptic crossmodal information retrieval. However, it remains unclear how LPPC subregions are involved in visuo‐haptic crossmodal retrieval processing. Methods: In the present study,  we used an fMRI experiment with a crossmodal delayed match‐to‐sample paradigm to reveal the functional role of LPPC subregions related to unimodal and crossmodal dot‐surface retrieval. Results: The visual‐to‐haptic condition enhanced the activity of the left inferior parietal lobule relative to the haptic unimodal condition, whereas the inverse condition enhanced the activity of the left superior parietal lobule. By contrast, activation of the left intraparietal sulcus did not differ significantly between the crossmodal and unimodal conditions. Seed‐based resting connectivity analysis revealed that these three left LPPC subregions engaged distinct networks, confirming their different functions in crossmodal retrieval processing. Conclusion: Taken together,  the findings suggest that functional heterogeneity of the left LPPC during visuo‐haptic crossmodal dot‐surface retrieval processing reflects that the left LPPC does not simply contribute to retrieval of past information; rather, each subregion has a specific functional role in resolving different task requirements. Abstract : Our findings have provided the knowledge that left lateral posterior parietal cortex subregions do not merely contribute to retrieving past information; rather, each subregion has a more specific functional role in resolving crossmodal retrieval requirements.